"Uncomfortable territory": personal and organisational values in the tax profession. Issue 1 (2nd January 2023) - Killian, Sheila; O'Regan, Veronica; O'Regan, Philip
ABSTRACT: As professionals, accountants hold a public interest mandate based in part on ethical claims. However, individual professionals, particularly in tax, commonly see their work as more technical than relating to the common good. Rising public concern about tax avoidance focuses attention on how ethical values are brought to bear on tax work. In these contexts, the tension between personal and organisational values merits attention. This study draws on a large international survey and a set of 68 semi-structured interviews to explore the balance between the personal ethical or spiritual values that individuals bring to their tax work and the ethical framing of their organisations. This direct approach captures self-reported moral awareness experienced at the level of the individual tax professional, framed by the concept of ethical awareness as a base level of ethical action (Rest, J., Moral development: Advances in research and theory . Praeger, 1986). We find, inter alia, that spiritual values are understood as personal and are most influential in smaller, more domestic firms and among those still undertaking professional exams, while ethical awareness is lowest among early career professionals in large international firms. The study highlights a disconnect between ethical learning acquired during professional training and its application at the early career stage. Socialisation within the firm adds to the potential for the early-career stage to set the tone for career-long ethical framing. This heightens the responsibility of firms as well as professional bodies to valorise moral judgement.